2006
DOI: 10.1080/13693780600876553
|View full text |Cite
|
Sign up to set email alerts
|

The pH signaling transcription factor PacC mediates the growth ofTrichophyton rubrumon human nailin vitro

Abstract: We report here the isolation, molecular cloning and initial characterization of the Trichophytonrubrum pacC gene, which encodes a putative protein that is homologous to the PacC/Rim101p family of pH signaling transcription regulators. The promoter region of the T. rubrumpacC gene contains four recognition sites 5'-GCCAAG-3' for the PacC protein, suggesting that the transcription of this gene itself could be induced under alkaline growth conditions. The enhanced expression profile of the T. rubrumpacC gene in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
22

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 10 publications
2
68
0
22
Order By: Relevance
“…The single gene deletion resulted in complete loss of the gene sequence (as detected by Southern blotting and PCR) and resulted in a mutant phenotype (altered growth), strong evidence that the genome of this strain is haploid. Similarly, two recent gene deletions from T. rubrum also suggest that the strain used in that analyses is haploid (10,12). This suggests that T. rubrum is haploid but not capable of mating.…”
Section: Tools For Hypothesis Generation In the Dermatophytesmentioning
confidence: 96%
See 1 more Smart Citation
“…The single gene deletion resulted in complete loss of the gene sequence (as detected by Southern blotting and PCR) and resulted in a mutant phenotype (altered growth), strong evidence that the genome of this strain is haploid. Similarly, two recent gene deletions from T. rubrum also suggest that the strain used in that analyses is haploid (10,12). This suggests that T. rubrum is haploid but not capable of mating.…”
Section: Tools For Hypothesis Generation In the Dermatophytesmentioning
confidence: 96%
“…Most recently, gene deletions have been obtained using protoplasting in M. canis (54) and in T rubrum (10,12). In the M. canis study, homologous recombination resulting in gene deletion was found in 2 out of 100 colonies screened-a low frequency of homologous recombination.…”
Section: Tools For Hypothesis Testing In the Dermatophytesmentioning
confidence: 99%
“…The pacC lineage of T.rubrum, which has this inactive gene, had its infectious capacity reduced when cultured in fragments of human nail, correlating with a sharp reduction of the keratinolytic activity. 29 These works suggest that development in keratin and the consequent degration of this protein are somehow regulated by the pacC gene, interfering with the secretion of proteases with optimal activity in alkaline pH. Moreover, pH signaling and monitoring pathways could be considered dermatophyte virulence factors, allowing the development and maintenance of the infection.…”
Section: Host-dermatophyte Interaction and The Pathogenesis Of Dermatmentioning
confidence: 99%
“…Genetic manipulation in dermatophyte research has been hampered by the limited number of available genetic tools and the lack of full genome sequences. Only a small number of genes have therefore been studied, and functional analysis by targeted gene disruption has been demonstrated only in a very few selected cases (6,7,35). High-throughput gene discovery by expressed sequence tag (EST) sequencing and cDNA-based microarrays provide additional valuable methodologies for the analysis of biological systems.…”
mentioning
confidence: 99%